2022
DOI: 10.1177/15248380221089981
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and Relationship Violence Among LGBTQ+ College Students: A Scoping Review

Abstract: Although there has been increased attention to campus sexual and relationship violence (SRV) because of Title IX and the #MeToo movement, much of that attention has focused on victimization of cisgender heterosexual women. This scoping review uncovers information from empirical studies on what is known about LGBTQ+ (e.g., lesbian, gay, bisexual, transgender, queer, and nonbinary) students’ experiences of campus SRV. Using rigorous scoping review methods (i.e., searches of 15 databases, searches of expert websi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 92 publications
1
20
0
Order By: Relevance
“…Most studies focus on medical students and not on all health students; therefore, our study provides new knowledge that nursing and physiotherapy students are the most at risk for GBV. We found also that being LGBTQ+ increases the risk of experiencing GBV [29] . As expected, the risk of GBV increases with the number of years of study [26].…”
Section: Discussionsupporting
confidence: 58%
“…Most studies focus on medical students and not on all health students; therefore, our study provides new knowledge that nursing and physiotherapy students are the most at risk for GBV. We found also that being LGBTQ+ increases the risk of experiencing GBV [29] . As expected, the risk of GBV increases with the number of years of study [26].…”
Section: Discussionsupporting
confidence: 58%
“…This conceptualization of gender “meant [transgender and nonbinary] people were overlooked at best, and dismissed at worst” (Marine & Nicolazzo, 2020, p. 5020). Despite calls for more LGBTQ+-affirming and -specific programing (Eisenberg et al, 2021; Klein et al, 2022; Marine & Nicolazzo, 2020; Potter et al, 2012), evaluations of such programs do not currently appear in the literature (Klein et al, 2022). In addition, both published research and key guidance documents for SRV prevention educators and administrators advocate for tailoring prevention efforts to meet the needs of minoritized communities including LGBTQ+ students but there is limited guidance on how to do so (American College Health Association, 2020; Campus Technical Assistance and Resource Project, 2016; DeGue et al, 2014; Dills et al, 2016).…”
Section: Cisheteronormativity and Campus Srv Preventionmentioning
confidence: 99%
“…Studies have also shown that RV victimization rates are likely similar to or higher for LGBTQ+ students compared to cisgender heterosexual students (Cantor et al, 2020; DeKeseredy et al, 2019; Graham et al, 2019; Klein et al, 2022). LGBTQ+ student survivors may suffer profoundly negative behavioral, emotional, academic, economic, and health outcomes that are exacerbated due to minority stress (Edwards & Sylaska, 2013; Klein et al, 2022; Mennicke et al, 2020; Meyer, 2003).…”
mentioning
confidence: 98%
See 2 more Smart Citations